2020
DOI: 10.2147/cmar.s253565
|View full text |Cite
|
Sign up to set email alerts
|

<p>DNAM1 and 2B4 Costimulatory Domains Enhance the Cytotoxicity of Anti-GPC3 Chimeric Antigen Receptor-Modified Natural Killer Cells Against Hepatocellular Cancer Cells in vitro</p>

Abstract: Purpose: Hepatocellular cancer (HCC) is the sixth most prevalent cancer and the third leading cause of cancer-related death worldwide. Cellular immunotherapy against glypican 3 (GPC3) has recently been used in the treatment of HCC, following the success of chimeric antigen receptor (CAR)-T therapy in treatment of B cell malignancy. However, CART cells are not "off-the-shelf" and always cause cytokine release syndrome, which can be eliminated by using natural killer (NK) cells as effector cells. Since a costimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…A study found that CAR-NK cells containing NK-specific, DNAM1 and/or 2B4 co-stimulatory receptors demonstrate higher cytotoxicity against several hepatocellular cancer cell lines (HEpG2, Hep3B, L-02, Huh7) than CAR-T cell-derived constructs. The tested CAR structures were CD3ζ alone, CD28.CD3ζ (CAR-T cell derived), DNAM1.CD3ζ, 2B4.CD3ζ and DNAM1.2B4.CD3ζ (DNAM1 and 2B4 are both NK-cell-specific co-stimulatory receptors), which had been transferred into NK92 cells and directed against the GPC3 antigen [ 60 ]. In addition, CAR-T structures were also compared with CAR-NK structures against neoplasms originating from T lymphocytes.…”
Section: The Therapeutic Mechanisms Of Car-nk Cellsmentioning
confidence: 99%
“…A study found that CAR-NK cells containing NK-specific, DNAM1 and/or 2B4 co-stimulatory receptors demonstrate higher cytotoxicity against several hepatocellular cancer cell lines (HEpG2, Hep3B, L-02, Huh7) than CAR-T cell-derived constructs. The tested CAR structures were CD3ζ alone, CD28.CD3ζ (CAR-T cell derived), DNAM1.CD3ζ, 2B4.CD3ζ and DNAM1.2B4.CD3ζ (DNAM1 and 2B4 are both NK-cell-specific co-stimulatory receptors), which had been transferred into NK92 cells and directed against the GPC3 antigen [ 60 ]. In addition, CAR-T structures were also compared with CAR-NK structures against neoplasms originating from T lymphocytes.…”
Section: The Therapeutic Mechanisms Of Car-nk Cellsmentioning
confidence: 99%
“…Consequently, based on signal activating potential, NK cell-specific co-stimulatory domains can be arranged in the order of DAP12 > CD3ζ > DAP10 [ 45 ]. Interestingly, a third generation of CAR NK cells containing DNAM1 and 2B4 has been shown to exhibit a much higher toxicity in hepatocellular carcinomas than CAR NK cells generated either with no co-stimulatory domain or with T cell-specific ones [ 63 ]. The upcoming fourth generation of armed CAR NK cells are engineered to co-express molecules such as cytokines with co-stimulatory domains to further improve functionality [ 8 ].…”
Section: Precise Design For a Functional Car Structurementioning
confidence: 99%
“…Notably, the GPC3-CAR-NK-92 cells were cytotoxic to GFP3-negative HCC cells. Huang et al [ 40 ] made a further modification to GPC3-CAR-NK-92 cells by replacing the intracellular domains of CD28 and CD3ζ with the costimulatory domains of DNAM1 and 2B4. DNAM1, also known as CD226, is a costimulatory receptor in cytotoxic T cells, NK cells, and monocytes[ 41 ].…”
Section: Car-nk Cells In Hcc Therapymentioning
confidence: 99%